Ground reaction forces on vibrating structures - Nhleko, S; Blakeborough, A; Williams, M (2009)
Due to world-wide reports and evidence that modern public structures can undergo perceivable motion as a result of rhythmic crowd excitation, the present study investigated the effects of structural vibration on ground reaction forces (GRFs) and the potential use of this data in structural engineering design. GRF data of several human subjects were measured on a fully instrumented grandstand whose motion can be controlled to simulate a vibrating seating deck. Subjects were requested to stand on a vibrating deck and give feedback on their state of comfort. At the same time, GRFs generated during standing on the vibrating deck, as well as the motion of the deck were recorded. Tests results indicate that there is a relationship between the state of comfort and GRFs generated during standing on the vibrating deck. In particular, it is confirmed that the human state of comfort can be related to the root mean square (RMS) of the normalized GRF time history - the normalized foot point acceleration time history. This is a new approach to the evaluation of human sensitivity to vibration motion, which is effectively based on the acceleration time history of the actual subject. The new approach based on the acceleration of the actual subject is shown to be more reliable than the traditional approach based on the acceleration of the supporting structure. Finally, the relationship presented here means that after calibration against the subjective responses, GRF data has a potential for use as an objective measure of the human state of comfort and thereby eliminate the subjective element associated with human judgment of his or her state of comfort. Alternatively, the calibrated GRF data can be used to supplement and validate responses obtained as subjective feedback from humans regarding their own state of comfort. © 2009 Society for Experimental Mechanics Inc.